New trends in biophotonics - Fábián, László; Mathesz, Anna; Dér, András (Acta Biologica Szegediensis, 2015)
Photonic structures offer a promising alternative of conventional electronic ones, especially for future information technological applications. Instead of conductors and transistors, their optical analogues (miniature light guides and optical switches, respectively) are serving as passive and active elements processing information in photonic circuits. One of the biggest challenges in this respect is to find proper nonlinear optical (NLO) materials that are able to actively control the flow of information in integrated optical (IO) circuits. Several inorganic and organic materials have been considered for this special application, requiring high speed, sensitivity, reliability and log-term stability. So far, however, none of them is regarded as the optimal solution. In 2002, we suggested an especially stable, light-sensitive biomaterial, the protein bacteriorhodopsin (bR), to be used as an active material in NLO structures of IO applications (Ormos et al. 2002). An IO switching and modulation using a bR adlayer on a grating-coupled planar optical waveguide was also demonstrated. This publication inspired a number of upcoming research papers dealing with the application of bR in different optical switch structures, defining a new trend in photonics, using hybride structures comprised of passive inorganic, and active biomaterials. Below, we give a brief overview of the relevant, recent results.